2021
DOI: 10.1007/s10895-021-02736-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen

Abstract: Employing natural or arti cial sunscreens is essential to protect the skin from ultraviolet radiations that cause premature aging and develop melanoma and other forms of skin cancer. The 2-Phenylbenzimidazole-5-sulfonic acid, commonly known as ensulizole is a water-soluble arti cial sunscreen that absorbs mostly UV-B (280 nm − 315 nm) radiations and protects the skin against the harmful effects of these radiations. Steady-state absorption indicates a strong absorption feature at 303 nm and a weak at 316 nm tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Further details of the measurements are given in our previously reported work. 35 Cyclic voltammetry (CV) curves are recorded using a CH1660B electrochemistry workstation.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Further details of the measurements are given in our previously reported work. 35 Cyclic voltammetry (CV) curves are recorded using a CH1660B electrochemistry workstation.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…5(f) and Table S1† showed that the average emission lifetime of FeVO 4 nanowires (32.78 ns) was much longer than FeVO 4 bulk (1.41 ns), which revealing that the recombination of photogenerated carriers was more restrained in FeVO 4 nanowires. 41…”
Section: Resultsmentioning
confidence: 99%
“…5(f) and Table S1 † showed that the average emission lifetime of FeVO 4 nanowires (32.78 ns) was much longer than FeVO 4 bulk (1.41 ns), which revealing that the recombination of photogenerated carriers was more restrained in FeVO 4 nanowires. 41 In the photocatalytic experiment, the separation and transfer of photogenerated charges restricted the reaction activity. One of the important factors is that the higher conductivity means that the photogenerated carriers will migrate to the surface of the catalyst more quickly to participate in the chemical reaction.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…The samples were excited with a pulsed LED laser source at 306 nm, and the PL was measured at room temperature as described in our previously reported work. 30 …”
Section: Characterizationmentioning
confidence: 99%
“… 29 2-Phenylbenzimidazole-5-sulfonic acid (PBSA), also recognized as “ensulizole”, is a renowned UV-B-type artificial sunscreen filter. 30 Previously, this compound was analyzed extensively as an environmental pollutant in the treatment of wastewater. 31 34 …”
Section: Introductionmentioning
confidence: 99%